Lupus activity in lupus nephritis patients with end-stage renal disease treated with hemodialysis - Caroline Samy Morad; Shams ElDoha Galal Zaiema; Eman Ahmed Hafez; Mohammed Maher Mohammed Mohammed Mansour; Amr Elsayed Mohammed Abd-Allah Khalil; Shaymaa Gamal Arafa Hassan (The Egyptian Journal of Internal Medicine)
Abstract Background Lupus nephritis is one of the major causes of ESRD, which may necessitate renal replacement therapy, especially hemodialysis. Evaluating post-HD lupus flares in LN patients is pivotal in improving their outcomes. This issue is still under consideration by researchers. This research analyzed lupus activity in LN patients with ESRD treated with HD. Methods A number of 70 LN patients diagnosed by renal biopsy were divided into age- and sex-matched two groups: They were divided into two groups: the HD Group, which were LN patients who progressed to ESRD treated with HD (n = 35), and the CKD Group, which contains LN patients’ stage III, IV by renal biopsies and HD free (n = 35). The non-renal systemic lupus erythematosus (SLE) disease activity index (nrSLEDAI) score was used to estimate lupus flares in both groups regardless of the stage of renal affection. Results The HD group exhibited considerably declined lupus activity compared to the CKD group, irrespective of the progression of renal pathology. With long-term period maintenance on HD, there was an obvious remission in both clinical and serological parameters of SLE recorded by the nrSLEDAI scoring system. Current doses of oral corticosteroids were less in the HD group than in the CKD group. Conclusion Using the nrSLEDAI score, our current research provides evidence of a reverse association between the longevity of hemodialysis (HD) and lupus activity, a "Cut-down phenomenon.” We believe that performing clinical trials and developing new post-HD evidence-based treat-to-target management guidelines for LN patients is now mandatory to improve their clinical outcomes and quality of life.